Impacts of knowledge sourcing on employee innovation: the moderating effect of information transparency. Issue 2 (7th September 2018) - Che, Tong; Wu, Zijing; Wang, Yaoyu; Yang, Rui
Abstract : Purpose: Innovation is the combination of idea generation and idea implementation. Sourcing relevant and credible external knowledge is critical for individuals to generate new feasible ideas and reduce the uncertainty of implementation. The purpose of this study is to investigate the effects of knowledge sourcing on employee's innovations behavior. Design/methodology/approach: The data were collected by paper-based survey in four Chinese companies' R&D departments and consisted of 569 valid responses. Structure equitation modeling method was used to test the hypotheses. Findings: The results indicate that knowledge sourcing, which is formatively conceptualized by tacit knowledge sourcing and explicit knowledge sourcing, significantly influences employee's innovation behavior. In particular, the direct effect of knowledge sourcing is fully mediated by task-efficacy. Furthermore, the effects of knowledge sourcing are contingent upon information transparency. Originality/value: This study not only contributes to knowledge sourcing literature by investigating knowledge sourcing from idea generation and idea implementation perspectives, but also is of importance to knowledge management research by demonstrating the moderating effects of information transparency.